A study on the preparation and characterization of maghemite (γ-Fe2O3) particles from iron-containing waste materials. Issue 4 (1st October 2020) - Rahman, Lutfor; Bhattacharjee, Shovon; Islam, Sydul; Zahan, Fauzia; Biswas, Bristy; Sharmin, Nahid
ABSTRACT: The recovery and repurposing of valuable substances from iron-bearing wastes is challenging and vital from economic and environmental perspectives. Herein, maghemite (γ-Fe2 O3 ) particles were synthesized from different iron-containing waste materials by simple chemical precipitation method using HCl, NaOH, and Na2 CO3, followed by calcination. Subsequently, the optimum pH value for the precipitation of iron from solution, and calcination temperature for getting γ-Fe2 O3 were found at 12 and 350°C, respectively. The final products were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), particle size analysis (PSA), thermogravimetry/differential thermal analysis (TG/DTA), and vibrating sample magnetometry (VSM). The formation of γ-Fe2 O3 was anticipated from XRD and FT-IR studies, while TG/DTA data supported their excellent thermal permanence. SEM studies showed that the γ-Fe2 O3 particles were relatively irregular, mostly spherical structured with a particle size ranged around 0.2–0.35 μm. PSA confirmed the high specific surface area of γ-Fe2 O3 particles, and the largest one was found from the iron dust. VSM measurement assured the existence of ferromagnetic properties in γ-Fe2 O3 particles at room temperature. The findings reveal that this procedure is a viable way to prepare γ-Fe2 O3 particles from iron-containing waste materials.